Budowa i struktura górnoreglowych borów świerkowych [Picea abies (L.) H. Karst] o charakterze pierwotnym w dolinach Jarząbczej i Pyszniańskiej (Tatrzański Park Narodowy) - Karczmarski, Jan; Bryniarska, Celina (Leśne Prace Badawcze, 2012)
The paper discusses two upper subalpine primary spruce [ Picea abies (L.) H. Karst] stands (permanent research plots), at an altitude of 1390-1450 m above sea level, in the Pyszniańska and Jarząbcza valleys of the Western Tatras (Tatra National Park). In 2006, the diameter at breast height (DBH) and height of living and dead trees were measured in these stands. Assessments were made of the length of crowns, according to IUFRO classification, and the trees’ developmental cohort (following Řehak 1964). Trunk length and mid-point diameter were measured from fallen dead trees and the degree of wood decomposition was recorded according to a three-stage classification index. Transects were established covering a specified number of regenerations, and a vertical and horizontal plan of stand structure was made. Volume of the studied stands was 479 m 3 ha -1 on the sample plots in Jarząbcza and 453 m 3 ha -1 in Pyszna, and number the of living trees ha -1 was 338 and 284, respectively. In the two stands, the largest spruces reached a DBH of 110 and 90 cm and height of 26.5 and 31.5 m, respectively. The DBH of living trees followed a unimodal and gamma distribution. Total volume of necromass on the sample plot was about 27 m 3 ha -1 in Jarząbcza and 157 m 3 ha -1 in Pyszna. The standing dead wood intensity secretion index (volume of necromass / living trees ha-1) was about 0.05 in Jarząbcza and 0.35 in Pyszna. In the Jarząbcza plot, the stand had a simple almost-one-storey structure (with 73% in the top layer), whereas the Pyszna stand had a complex structure, with slight predominance of the upper layer (56%). Regeneration in both studied stands was dominated by Sorbus aucuparia L. (about 2.7–6.5 thousand trees ha-1) with the occasional occurrence of undergrowth of Picea abies (6-8 trees ha -1 ). The study plots’ specific characters indicate that the stand in Jarząbcza is at its optimal developmental stage, whereas in Pyszna the stand has reached the first stage of decay.